2012
DOI: 10.1126/science.1213229
|View full text |Cite
|
Sign up to set email alerts
|

Direct Kinetic Measurements of Criegee Intermediate (CH 2 OO) Formed by Reaction of CH 2 I with O 2

Abstract: Ozonolysis is a major tropospheric removal mechanism for unsaturated hydrocarbons and proceeds via "Criegee intermediates"--carbonyl oxides--that play a key role in tropospheric oxidation models. However, until recently no gas-phase Criegee intermediate had been observed, and indirect determinations of their reaction kinetics gave derived rate coefficients spanning orders of magnitude. Here, we report direct photoionization mass spectrometric detection of formaldehyde oxide (CH(2)OO) as a product of the reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

50
732
6
11

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 662 publications
(799 citation statements)
references
References 50 publications
50
732
6
11
Order By: Relevance
“…A series of more recent laboratory and theoretical studies also presented a wide range of recommendations for the reaction rates of R 5 . Welz et al 12,44 reported a significantly higher upper limit for k R5 (k R5a+R5b = 4 × 10 −15 molecules cm 3 s −1 ) compared to the 9 × 10 −17 molecules cm 3 s −1 from Stone et al 13 Stone et al 13 also experimentally derived k R5a (5.4 × 10 −17 molecules cm 3 s −1 ), very close to that applied in MCM 3.2. Theoretical studies 45,46 evaluating the kinetics of sCI with water dimer argue that a reaction with water dimer becomes the dominant sCI chemical sink especially for the small sCI.…”
Section: ■ Results and Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…A series of more recent laboratory and theoretical studies also presented a wide range of recommendations for the reaction rates of R 5 . Welz et al 12,44 reported a significantly higher upper limit for k R5 (k R5a+R5b = 4 × 10 −15 molecules cm 3 s −1 ) compared to the 9 × 10 −17 molecules cm 3 s −1 from Stone et al 13 Stone et al 13 also experimentally derived k R5a (5.4 × 10 −17 molecules cm 3 s −1 ), very close to that applied in MCM 3.2. Theoretical studies 45,46 evaluating the kinetics of sCI with water dimer argue that a reaction with water dimer becomes the dominant sCI chemical sink especially for the small sCI.…”
Section: ■ Results and Discussionmentioning
confidence: 54%
“…Therefore, if we include the fast water dimer reaction in the zero-dimensional model calculation, it results in no contribution to H 2 SO 4 formation from R4. For comparison purpose, we calculated CH 2 OO with the upper limit of k R5 presented by Welz et al 12 The results shown in Figure 3c suggest significant suppression in CH 2 OO by applying the fast k R5 , which would cause substantially less contribution of the sCI reaction channel to H 2 SO 4 formation. Further studies on chemical interactions between water vapor and sCIs are urged in this context.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…4,13 Welz et al 4 reported an efficient way to prepare Criegee intermediates. For example, CH 2 OO can be prepared via (R6) + (R7a).…”
Section: O( 1 D) + H 2 O -2oh (R5)mentioning
confidence: 99%
“…Now it is generally accepted that ozonolysis of alkenes proceeds via Criegee intermediates, highly reactive species postulated in 1949 by Rudolf Criegee. 1,2 In the troposphere, Criegee intermediates are involved in several important atmospheric reactions, 3 including reactions with SO 2 and NO 2 , [4][5][6][7] or can be photolyzed by near UV light, [7][8][9][10] as shown for CH 2 The formation of SO 3 and NO 3 , as in (R2) and (R3), plays an important role in atmospheric chemistry, 11,12 including aerosol and cloud formation. The formation of O( 1 D), as in (R4), will result in OH formation through (R5).…”
mentioning
confidence: 99%
“…15−28 A key reaction in atmospheric chemistry is that of water with the stabilized Criegee intermediate. [18][19][20][21][22][23][25][26][27]29,30 It is known that this reaction leads to the formation of hydroxyalkyl hydroperoxide, carboxylic acids, carbonyl compounds, and H 2 O 2 , 4,6,31−33 species with important environmental implications. In particular, H 2 O 2 is a molecule of broad tropospheric and biological relevance.…”
Section: Introductionmentioning
confidence: 99%